Some remarks on the Sumudu and Laplace transforms and applications to differential equations - Kilicman, Adem; Eltayeb, Hassan (Hindawi Publishing Corporation, 2012)
We study the relationship between Sumudu and Laplace transforms and further make some comparison on the solutions. We provide some counterexamples where if the solution of differential equations exists by Laplace transform, the solution does not necessarily exist by using the Sumudu transform; however, the examples indicate that if the solution of differential equation by Sumudu transform exists then the solution necessarily exists by Laplace transform.